Effect of Extraction Time on Unreacted Oil Removal in Biodiesel Purification Using Deep Eutectic Solvent - Helda Niawanti; Siti Zullaikah (Reaktor, 2018)
Rice bran oil (RBO) based biodiesel contains unreacted oil such as monoglyceride (MG), diglyceride (DG) and triglyceride (TG) to be purified. The liquid-liquid extraction (LLE) method was used for purification using Deep Eutectic Solvent (DES). The objective of this work was to study the effect of extraction time on unreacted oil removal. RBO containing 16.49% oil with free fatty acids (FFA) content of 44.75%. Acid catalyzed methanolysis was used for biodiesel production under operating conditions: T = 60°C, t = 8 hours, molar ratio of oil/methanol  was 1/10, H2SO4 1% w/w of RBO. Crude biodiesel containing 89.05% fatty acid methyl ester (FAME), 0.05% FFA, TG 4.03%, DG 4.01%  and MG 0.30%. DES was made from choline chloride and ethylene glycol with 1/2 molar ratio, while molar ratio of biodiesel/DES was 1/2. The extraction time was varied from 15 to 240 minutes at 30°C. The highest TG, DG and MG removal were obtained at 240 minutes, they were 3.01%, 0.22% and 0.03%, respectively. FAME and FFA content were 96.55% and 0.03%. Keywords: biodiesel; DES; extraction; unreacted oil; purification